Sisal: sistema produtivo, fundamentos sociais e técnicos das políticas na Bahia - FIGUEIRÊDO, Maria Gorete Borges (2016)
This study aims to analyze the sisal productive system inserted in Sisal Territory, located in Bahia's semi-arid. This region brings in the midst of its history a process of farm and a contradiction, since the sisal activity have been over years, identified as sustainable, and now show clear signs of stagnation. Associative practices, cooperative and public policies have been established over the last decades seeking to strengthen the productive sector and the valuation of sisal activity. However, it is clear that research the urgency of restructuring the whole production system, from insertion demands of technological innovations that pass through cultivation, multiplication of seedlings, leaf shredding, extending to the use of sisal waste; as well as the structuring of an effective service system; incentives to producers and the continuation of local textile industries, and is therefore subject to this culture, soon extinguish sisal while economic activity in Bahia.